SOEP-IS 2016.2 - HBRUTTO: Householdrelated gross file - DIW Berlin / SOEP (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
The hbrutto dataset contains household-related information (of the gross sample) which is not asked in the household questionnaire but is instead generated by the interviewers during fieldwork.
Keywords: 330